(untitled) (Biocenosis, 2015)
Regenerating forests may allow some species of mature forest birds can disperse and use resources such temporary habitat. Were identified mature forest bird species that frequent patches in regeneration by the point count method. Bird abundance was higher in the regenerating forest. The average abundance of Ramphastidae, tanager and Icteridae was higher in regenerating forests. Were recorded 48 species in the mature forest and 36 species in the regenerating forest. The regenerating habitat shared 42.8% of mature forest species, of which 29 were in the canopy. The birds may depart from mature forest to exploit the abundance of fruits and arthropods of secondary growths. Abundance; Birds; Ecology; Richness